Hermeneutic Rationality and the Heuristic Dimension of African Philosophy - (:unkn) unknown (CCSD, 2025)
International audience
Keywords: African Research; Philosophy in Africa; African philosophy; Philosophie en Afrique; Hermeneutic rationality; Hermeneutic turn